(Still) supporting the indispensable power: Singapore's relations with the United States from Trump to Biden - Tan, See Seng (2022)
Singapore regards the United States as an indispensable power whose global might, purpose, and reach Singaporeans have long viewed as invaluable to the stability, security, and prosperity of Asia. The United States has evolved from an unlikely collaborator and patron of Singapore following the 1971 British withdrawal east of the Suez Canal to being the city-state’s invaluable partner today. As with other U.S. allies and partners, Singapore’s relations with the United States were tested during the presidency of Donald Trump, who effectively recused his nation from the traditional role of global leadership it had played since the end of World War II. Yet Singapore chose to stay the course of its pragmatic encouragement and facilitation of the U.S. forward presence in Asia. The transition to the Biden administration, which presumably aims to walk back Trump’s “America first” policy without easing up on China, has not changed Singapore’s perspective on and policy toward the United States. It remains in Singapore’s interest to continue welcoming, facilitating, and—in the face of growing Chinese objection to U.S. strategic dominance in the region—justifying the United States’ place and role in Asia.